Sexting Among Adolescents: The Emotional Impact and Influence of the Need for Popularity - Del Rey, Rosario; Ojeda, Mónica; Casas, José A.; Mora-Merchán, Joaquín A.; Elipe, Paz (Frontiers in Psychology, 2019)
Sexting refers to the exchange of sexual content material via technological devices. The definitions of this phenomenon vary greatly, mainly, depending on the types of sexting: primary and secondary. Besides the above, there is no common perspective on whether sexting is a risk behavior that entails some type of impact by itself or not and, in such a case, whether this impact varies according to gender. In addition, the need to be popular has shown to be a factor that could increase the probability of being involved in sexting. The present study analyses the potential emotional impact of sexting as well as the effect of the need for popularity on this phenomenon and if it varies according to the gender. The sample comprised 2356 high school students (46.8% female, 53.2% male; age range 11 to 18 years old, M = 13.72; SD = 1.31) belonging to 12 compulsory secondary education (ESO) schools from the South of Spain. To assess sexting implication four questions were presented to participants (sending, receiving, forwarding and receiving sexts via intermediary). Scales, self-report, about emotional impact (depressed, annoyed and active) and need for popularity were also applied. The results obtained show that, although sexting has a clear emotional impact on adolescents, it does not appear to generate a negative impact among those involved, at least in the short-term. Concretely, this phenomenon seems to trigger emotions related to activation in boys and girls (I feel lively, energetic, satisfied, ready, determined, active). Additionally, with respect to the need for popularity, its relevance, specially, in relation to active emotional impact has been confirmed by the analyses. Statistical models found for boys and girls were similar. In addition, some differences in emotional impact by gender were found, girls feeling more depressed and annoyed in secondary sexting, and boys more active regarding both types of sexting.